The Jurisprudence from Aharon Barak: Views from Europe - DE VISSER, Maartje (Institutional Knowledge at Singapore Management University, 2011)
At the Montesquieu Seminars, new developments in legal theory are explored and discussed. Fundamental problems experienced in the (practices of) law are reflected critically. A broad range of disciplines contribute at these attempts of sustained critical reflection. No particular school of legal theory is preferred over another. Tilburg Law School has an open mind for new approaches to law and does not want to limit the debate to the agenda set by some school, movement, or discipline. As a result, while the seminars are conceived around urgent actual problems, the focus is interdisciplinary. Due to this, the Montequieu Seminars are especially interesting for national and local politicians, students, policy makers, advisory bodies, entrepreneurs, business management, advocacy, judiciary, and government. This book contains a written version of the seventh Montesquieu seminar, which was held in September 2010 by Aharon Barak.